Perceived Importance of the Factors Affecting Consumers’ Purchase of Sports Brands - Hassan, Ahmadsalim (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The sports brands and sports product market is an ever growing industry that generates billions of dollars yearly. Sports marketers have constantly faced the challenge of fully understanding consumer behaviors and factors that influences the choice of sports brands and the purchase of its products. This study investigates the importance of sports brand selection factors and how they vary amongst some demographic segments such as gender, age group, education level, sports brand preference, level of engagement in sports and preferred method of shopping (online or stores). The result showed that there is a significant difference between genders with respect to some of the general selection factors. It also showed a significant difference within each of the other demographic segments which are education level, age groups, level of engagement in sports, sports brand preference and preferred method of shopping all with regards to the general selection factors. The study also points out which element within each of the demographic segments places more importance of the general selection factor. Keywords: Brands, sports, sports brands, selection factors

ÖZ: Spor markaları ve spor ürünleri pazarı milyarlarca dolar üreten ve sürekli olarak büyüyen bir endüstri olarak karşımıza çıkmaktadır. Spor pazarlamacıları, tüketici davranışları ve spor markalarının seçimini ve ürünlerinin satın alımını etkileyen faktörlerin neler olduğunun anlaşılması konusunda zorluklarla sürekli olarak karşı karşıya kalmaktadır. Bu çalışma, spor markası seçim faktörlerinin önemini, cinsiyet, yaş grubu, eğitim düzeyi, spor markası tercihi, spora katılım düzeyi ve tercih edilen alışveriş yöntemi (çevrimiçi veya mağazalar) gibi bazı demografik faktörler arasında nasıl farklılık gösterdiğini araştırmaktadır. Çalışamda elde edilen sonuçlara bakıldığında, bazı genel seçim faktörlerine göre cinsiyetler arasında anlamlı bir fark olduğunu göstermektedir. Ayrıca, genel seçim faktörleri bakımından, eğitim düzeyi, yaş grupları, spora katılım düzeyi, spor markası tercihi ve tercih edilen alışveriş yöntemi olan diğer demografik faktörlerin her birinde önemli bir farklılık gösterdiği görülmektedir. Çalışmada ayrıca, demografik faktörler arasında hangi öğenin genel seçim faktörlerini daha fazla etkilemekte olduğu ortaya konulmaktadır. Anahtar Kelimeler: Markalar, spor, spor markaları, seçim faktörleri
Master of Business Administration in Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2019. Supervisor: Assist. Prof. Dr. Doğan Ünlücan.
Keywords: Business Administration; Sports Brands--sponsorship; Brands; sports; sports brands; selection factors